La UNCTAD y la promoción internacional de la competencia - Roca Tavella, Santiago (2011)
Through this article, the author shows us the implications for the protection of Competition, not only from a national level but also at an international level. These implications are based on the work being carried out by the United Nations Conference on Trade and Development - UNCtad, although in its origin had various activities, currently it is carrying out activities in favor and promotion of the Competition. In this sense, it should be noted that these activities vary depending on each country, and may be countries without Competition or consumer laws or authorities, countries with Competition laws and authorities that are just beginning, or developing countries with moderate experience, as is our case. This article not only shows us the successes of this body but also its weaknesses, among them on FTAs, where in the case of developing countries there is a lack of support and abandonment in the negotiation. Finally, an interview is conducted with the author about the topics discussed in this article.